2020
DOI: 10.1038/s41598-020-61775-9
|View full text |Cite
|
Sign up to set email alerts
|

Slco2a1 deficiency exacerbates experimental colitis via inflammasome activation in macrophages: a possible mechanism of chronic enteropathy associated with SLCO2A1 gene

Abstract: Loss-of-function mutations in the solute carrier organic anion transporter family, member 2a1 gene (SLCO2A1), which encodes a prostaglandin (PG) transporter, have been identified as causes of chronic nonspecific multiple ulcers in the small intestine; however, the underlying mechanisms have not been revealed. We, therefore, evaluated the effects of systemic knockout of Slco2a1 (Slco2a1 −/−) and conditional knockout in intestinal epithelial cells (Slco2a1 ΔIEC) and macrophages (Slco2a1 ΔMP) in mice with dextran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…(Mortimer, Moreau, Mac-Donald, & Chadee, 2016;Sokolowska et al, 2015). However, other authors report positive effects of PGE 2 upon NLRP3 inflammasome activation and IL-1β production in macrophages and monocytes under various stimuli (Nakata et al, 2020;Sheppe et al, 2018;Zasłona et al, 2017). Taken together, these findings indicate contextdependent modulation of NLRP3 inflammasome activation by PGE 2 .…”
Section: Pge 2 On Il-6 Productionmentioning
confidence: 94%
See 1 more Smart Citation
“…(Mortimer, Moreau, Mac-Donald, & Chadee, 2016;Sokolowska et al, 2015). However, other authors report positive effects of PGE 2 upon NLRP3 inflammasome activation and IL-1β production in macrophages and monocytes under various stimuli (Nakata et al, 2020;Sheppe et al, 2018;Zasłona et al, 2017). Taken together, these findings indicate contextdependent modulation of NLRP3 inflammasome activation by PGE 2 .…”
Section: Pge 2 On Il-6 Productionmentioning
confidence: 94%
“…PGE 2 was reported to inhibit NLRP3 inflammasome activation in macrophages through EP4 receptors, and blockade of COX‐2 or EP4 receptors resulted in increased NLRP3 inflammasome activation (Mortimer, Moreau, MacDonald, & Chadee, 2016; Sokolowska et al, 2015). However, other authors report positive effects of PGE 2 upon NLRP3 inflammasome activation and IL‐1β production in macrophages and monocytes under various stimuli (Nakata et al, 2020; Sheppe et al, 2018; Zasłona et al, 2017). Taken together, these findings indicate context‐dependent modulation of NLRP3 inflammasome activation by PGE 2 .…”
Section: Pgs In Covid‐19: Possible Immunopathological Mechanismsmentioning
confidence: 97%
“…This might be due to differences in the PGE 2 metabolic activities between mice and humans. Further, although recent studies have shown that SLCO2A1 function is lost in patients with CEAS, Slco2a1- deficient mice do not spontaneously develop enteritis [ 28 ]. This might be because Slco2a1 / SLCO2A1 has different functions in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…GSTT1 is found to alleviate colitis by the IL-22 dependent pathway [ 43 ]. SlCO2A1 deficiency is identified to deteriorate intestinal inflammation by activating the NLRP3 inflammasome in macrophages [ 44 ]. For the reasons above, the up-regulated CYP1A1 , SLC6A4 , SLC6A8 , PHLPP2 , ANO1 , NR1D1 , CPA6 , GLP-2R , GSTT1 and SlCO2A1 in mEV−fed mice indicated that mEVs facilitated the expression of genes that had low expression in colitis, and hence ameliorated colitis.…”
Section: Discussionmentioning
confidence: 99%